Beejal is solving y/7-3=39. As a first step, he starts by adding. To both sides of the equation, and then continues by multiplying by. On each side.

1 answer

Beejal starts by adding 3 to both sides of the equation to isolate y:

(y/7) - 3 + 3 = 39 + 3

Simplifying, we get:

y/7 = 42

Since y is divided by 7, Beejal continues by multiplying both sides of the equation by 7 to solve for y:

7 * (y/7) = 42 * 7

Simplifying further, we have:

y = 294

Therefore, the solution to the equation is y = 294.